The Willingness to Pay for Preventing Environmental Damage - Benno Torgler; María A. García-Vali\~nas (Center for Research in Economics, Management and the Arts (CREMA), 2005)
Since the 70s, an increasing number of studies investigating environmental preferences have been made. However, papers related to a country and its regions or its development over time are still largely lacking, although it is a promising line to search empirically for factors that have been strongly neglected in previous studies. This paper therefore aims at reducing such shortcomings, and analyzes the willingness to pay (WTP) in Spain and its regions for the periods 1990, 1995 and 1999/2000, with data from the World Values Surveys and the European Values Surveys. The results indicate strong regional differences and strong differences between the first and the second half of the 90s. This paper also shows the relevance of strongly neglected variables such as political interest and social capital.
Keywords: Q26; R22; Z13; I21; 330; Environment; Willingness to Pay; Regional and Time Preferences; Political Interest; Social Capital